Health promotion behaviors and quality of life among cancer patients : a systematic review - Ledinski Fičko, Sanja (Array, 2019)
Background: Multiple health behavior change interventions, especially promoting the improvements in diet and exercise behaviors, have been used to ameliorate the adverse effects of cancer and its treatment. It is a well known fact that healthy lifestyle has a significant impact on cancer cases. The group of people which are at a high risk of cancer are smokers, people with low fruit and vegetable intake, people with a drinking problem and with low physical activity. In 43% of the cases the incidence of cancer can be prevented by conducting adequate measures. Aim: The aim of this study is an overview of health promotion behaviors such as non-smoking, non-alcohol abuse, physical activity, diet and body weight and their impact on quality of life among cancer patients and cancer survivors. Methods: Literature overview was made systematically. Studies that have been included in the final analysis, were analyzed through 4 steps. After reviewing the abstract, 6 full text articles were examined in more detail for eligibility and were included in the final data analysis. Results: All six articles have shown that patients with healthy lifestyle and those who are conducting health promotion behaviors have greater score on the quality of life questionnaire. Physical activity has an impact on symptoms of treatment and disease. Conclusion: This study supports the need for future research on public health view on conducting healthy lifestyle during therapy and in the remission of disease. Health promotion behaviors have great impact on quality of life among cancer patients and cancer survivors.